The Role Of Critical Information On Self-Induced Competitiveness - Rosdini, Dini; Ritchi, Hamzah (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2019)
Competence and expertise improvement of accounting students in the global era are inevitable. Competition, particularly among accountants accross countries has now become a phenomenon to face from domestic professionals’ view point. Yet, this recent regional dynamic appears to bring little awareness on accounting students. The current research aims to test the influence of vital Asean Economy Community competition information on the motivation of accounting students in the learning process through experiments oriented toward internal validity reinforcement. The sample obtained were 85 participants accounting students on their second year who had passed the course on Introduction to Accounting.The research aimed to find out how critical information, through motivation, was capable of providing resources and momentum to students as a control perception of their behavior to improve accounting or non-accounting competence. It was expected that the research could provide empirical evidence on accouting students’ motivation related to competition information in the framework of TPB. The results indicate that critical competition information could increase motivation and skills of accounting students. Specifically, the research is expected to contribute in competence-based curriculum development through motivational aspect of competition information and can give suggestions to lecturers of accounting study program on factors affecting the motivation of accounting students in preparing for challenging working world. Peningkatan kompetensi dan keahlian mahasiswa akuntansi di era globalisasi saat ini merupakan suatu keniscayaan yang tidak dapat dielakkan dan harus dilakukan. Saat ini kompetisi khususnya dengan para akuntan dari negara lain sudah menjadi fenomena yang dihadapi. Namun, fakta mengenai kompetisi ini bisa saja belum disadari sepenuhnya oleh para mahasiswa akuntansi. Penelitian ini bertujuan untuk menguji pengaruh informasi kompetisi vital Masyarakat Ekonomi Asean (MEA) terhadap motivasi mahasiswa akuntansi dalam proses belajar melalui metode eksperimen yang berorientasi pada penguatan validitas internal. Sampel dalam penelitian ini adalah 85 partisipan mahasiswa akuntansi tahun kedua dan telah lulus mata kuliah Pengantar Akuntansi. Penelitian ini juga mencoba melihat bagaimana informasi kritikal, melalui motivasi, mampu menyediakan sumberdaya dan daya gerak bagi mahasiswa sebagai wujud persepsi kendali keperilakuan mereka, untuk meningkatkan kompetensi akuntansi dan non akuntansi mereka. Penelitian ini berkontribusi dalam memberikan bukti empiris mengenai motivasi mahasiswa akuntansi dikaitkan dengan informasi kompetisi yang mereka terima dalam kerangka Theory of Planned Behavior (TPB). Hasil penelitian ini menunjukkan bahwa informasi kompetisi kritikal dapat meningkatkan motivasi dan keahlian akuntansi para mahasiswa. Penelitian ini secara khusus diharapkan memberikan kontribusi dalam penyusunan kurikulum berbasis kompetensi dengan mempertimbangkan aspek motivasi terkait informasi kompetisi ini dan memberikan masukan kepada seluruh pendidik di perguruan tinggi khususnya program studi akuntansi mengenai faktor yang dapat memengaruhi motivasi mahasiswa akuntansi dalam proses belajar dan mempersiapkan diri di dunia kerja yang penuh tantangan.